Pengaruh Social Media Use dan Perceived Scarcity terhadap Impulsive Buying Produk Blind Box Pop Mart pada Generasi Z di Jakarta dengan Fear of Missing Out (FOMO) sebagai Variabel Mediasi - Anathalia Arshanti Badarudin (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of Social Media Use and Perceived Scarcity on Impulsive Buying of Pop Mart blind box products among Generation Z in Jakarta, with Fear of Missing Out (FOMO) as a mediating variable. A quantitative approach with a survey method was employed, involving 160 Generation Z respondents aged 14–29 years, domiciled in Jakarta, actively using social media, and having made impulsive purchases of Pop Mart blind box products, selected through purposive sampling. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that Social Media Use has a positive and significant effect on both FOMO and Impulsive Buying. Perceived Scarcity also has a positive and significant effect on FOMO and Impulsive Buying, although with a relatively smaller contribution. FOMO has the largest direct effect on Impulsive Buying. Furthermore, FOMO is proven to act as a partial mediating variable. The model explains 82.7% of the variance in Impulsive Buying. These findings confirm that the combination of digital stimuli and product scarcity perception shapes FOMO, which drives impulsive buying behavior among Generation Z, consistent with the Stimulus-Organism-Response framework.